Investigation of the leaching behavior of Na and Si in simulated HLW borosilicate glass obtained from the waste of a 1000 MWe class PWR reactor: using the response surface method - Hosseinpour Khanmiri, Mohammad; Yadollahi, Ali; Samadfam, Mohammad; Sepehrian, Hamid; Outokesh, Mohammad (Frontiers in Chemistry, 2024)
The immobilization of high-level nuclear waste (HLW) in glass waste matrices provides the key safety function of slowing down radionuclide emissions from an underground disposal site. This study examines the leaching behavior of two major elements, Na and Si, in HLW borosilicate glass simulated from waste of a 1000 MWe class pressurized water reactor (PWR) using response surface methodology and Box-Behnken Design. The design of the experiment was carried out considering three independent variables: the pH of the solution, the contact time, and the leaching temperature, leading to 17 leaching runs performed using the static product consistency test (PCT). The results of statistical analysis (ANOVA: analysis of variance) indicated that the effects of the individual variables and the interactions between them were statistically significant, and the relative consistency of the data further confirmed the model’s applicability. Data obtained from the PCT experiments revealed that the leaching behavior of Na and Si in the evaluated waste glass exhibited similar behavior to previously researched glasses for each condition tested.